Multi-person interaction in collaborative virtual conference for Metaverse - Yingying Li; Ajune Wanis Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Virtual conferences have successfully solved the challenges of traditional face-to-face conferences that can’t be carried out smoothly due to issues such as venue, transportation, and the pandemic. More importantly, as virtual conferences continue to develop and mature, they provide a virtual environment for multi-person collaboration, which is impossible to achieve with traditional face-to-face conferences. This technological innovation is expected to bring significant cost savings to various fields such as medical care, education, and industry. This paper proposes a unity-based multi-party collaborative virtual conference model. The model takes automobiles as the theme, which can realize the design and modification of the appearance of the automobiles by multiple people in the same space, and also supports operations such as the disassembly and installation of the automobile engine. This model is designed to deepen our understanding of multi-person collaboration capabilities in virtual conferences, a feature that is expected to significantly improve teamwork efficiency.